SabellaBySya / Nor Syahdani Zulkifli - Zulkifli, Nor Syahdani (2021)
SabellaBySya is a retail business where delivering the biggest solution to the fellow working moms as well as student to ease their process to get ready and getting dress by ditching the ironing process to get a perfect looks. The main intention and goals of SabellaBySya is to offering the high-end quality fabric and looking astonish effortlessly. This is due to our main speciality in developing an ironless fabrics. We also fulfilling our consumers satisfaction by having a variety of designs to choose from. Aside from that, SabellaBySya started the business in 1 st June 2021. The business is mainly using Facebook (FB) as the major platform to promote and market the product due to our main target is the millennials and adult men and women which more relatable to the use of our product specialty to ease their daily routine as a full time students and workers. The demand of SabellaBySyah designs also shown that the product is well delivered and recognized by the consumers to keep on purchasing more designs as well as share it with the loved ones. Our promotion strategies definitely attract more potential buyers which is give benefits to both parties which is giving us more sales and for the buyers to get the experiences trying different designs and style with a lower cost.